DETERMINAN AKUNTABILITAS KEUANGAN DANA DESA PASCA PENERAPAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 - I Made Laut Mertha JAYA (UNIB Press, 2019)
Village existence is very important for national development. Thus, uneven development between the Village and the City can cause many villagers who try their fortune in the city, leave the village and do not want to return to the Village. This research was conducted to determine the effect of human resource competence on financial accountability of village funds and the influence of the role of village heads on village financial accountability. The population in this study are all villages in the Sleman Regency. This research uses incidental sampling. The sample size uses the Slovin formula, with a minimum number of respondents of 71 villages. The analysis method uses structural equation modeling (SEM) analysis test. The conclusion of this study, namely that there is a significant influence between HR competencies on village financial accountability, meaning that if HR competencies are higher, the financial accountability of village funds is more accountable. There is a significant influence between HR competencies on the financial accountability of village funds, meaning that if HR competencies are higher, the financial accountability of village funds will be more accountable. There is a significant influence between the role of the village head on the financial accountability of village funds, meaning that if the role of the village head is higher, then the financial accountability of village funds is more accountable.